ESTHETIC IMPACT OF TOOTH EXTRACTION IN PAKISTANI PATIENTS - Hassan, Sohaib; Shaikh, Attiya; Fida, Mubassar (Journal of Ayub Medical College Abbottabad, 2014)
Background: The norms of Pakistani female patients differ from other Asian patients, this difference should be considered during diagnosis and treatment planning and they should be treated with different protocols in terms of tooth extraction and non-extraction treatments. The present study will provide clinical guidelines to assist in the decision-making process for borderline patients when considering extraction or non-extraction in the orthodontic treatment plan. Methods: Panels of 40 dentists and 40 laypersons evaluated randomly presented pre-treatment and post-treatment soft-tissue profiles of 30 extraction and 30 non-extraction female patients. Borderline patients were selected based on their initial diagnostic records. Two panels were asked to compare the pre-treatment and post-treatment soft tissue profile tracings and to quantify their perceptions of the aesthetic impact of treatment change using a visual analogue scale (VAS). Results: The mean VAS scores of dentists and laypersons for extraction treatment strategy were +23.03±27.89 and +19.41±26.79 mm (p=0.182) respectively. For non-extraction treatment strategy, mean VAS scores of dentists and laypersons were +12.51±26.56 and +14.55±21.22 mm (p=0.448) respectively. The mean change in lower lip protrusion after extraction treatment was 2.15±3.38 mm (p=0.002) and after non-extraction treatment was 0.83±2.75 mm (p=0.109). Conclusions: No significant difference was found between dentists and laypersons in their perception of aesthetic impact of a treatment strategy. There was significant change in lower lip protrusion only after the extraction treatment strategy. Keywords: Aesthetic impact, treatment strategies, borderline patients, Pakistan